Exploring access to financial services by visually impaired people - Sam Goundar; Milind Sathye (Journal of Risk and Financial Management, 2023)
Though consumers with vulnerabilities, such as visually impaired or blind and partially sighted people (BPSP), face several marketplace problems and challenges, existing literature provides limited guidance. The present study aims to examine the issues faced by BPSP in accessing financial services in Fiji. The study is grounded in the digital divide literature and reports that BPSP do face many hurdles in accessing financial services. We suggest that appropriate policies and industry initiatives could help mitigate the severe vulnerability faced by this cohort of the population in Fiji. We envisage that similar studies in other developing countries are required on an urgent basis to understand the international ramifications of the problem.
Keywords: 650; digital access; digital banking; digital divide; disability ICT; financial development; financial inclusion; financial services; visually impaired digital banking access